Morocco : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Morocco. (IMF Staff Country Reports; Country Report, 2018)
This 2017 Article IV Consultation highlights that economic growth in Morocco has picked up in 2017 and is expected to reach 4.4 percent, mostly driven by a significant rebound in agricultural activity while nonagricultural activity remains subdued. The unemployment rate increased to 10.6 percent in Q3:2017 (year-over-year) while youth unemployment remains high at 29.3 percent. Headline inflation (year-over-year) is expected to decline to 0.6 percent in 2017, reflecting lower food prices. Following a marked deterioration in 2016, the current account deficit is projected to improve in 2017 to 3.9 percent of GDP. This primarily reflects Morocco's global environment, particularly the stronger recovery in Europe, and strong export growth, mostly owing to the good performance of food product and phosphate and derivatives exports.